Effects of Treadmill Training in chronic hemiparetic: a randomized, double-blind clinical trial - Gomes, Wildja de Lima; Dias, Luciara Irene de Nadai; Guimarães, Rachel Paes; Stivali, Cínthia Mara; Faria, Gisele da Rosa; Bovi, Ana Carolina Nunes; Cacho, Ênio Walker de Azevedo; Cacho, Roberta de Oliveira; Lima, Núbia Maria Freire Vieira (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: It is estimated that the prevalence of cerebrovascular accident (CVA) increases significantly as a result of the increase in the elderly population, leading to dependence and care. Interventions with physical exercises are essential for patients with chronic CVA and hemiparesis to contribute to functional motor recovery. The gait of the hemiparetic patients is very impaired, including decreased speed, unipodal support in the abbreviated paretic limb, increased step length, decreased hip flexion, increased knee flexion and plantar flexion and involves compensatory strategies to deal with deficits of the affected limb. Rehabilitation programs of patients with CVA should focus on the restoration of the individual’s independence and ability to move. Objective: To analyze the effects of the addition of a load on a lower limb not affected in the discharge of weight and motor function of paretic lower limb. Method: Experimental, randomized, double-blind study conducted at the Physiotherapy and Occupational Therapy Outpatient Clinic of the Hospital das Clínicas (HC) - UNICAMP. Participants were assessed by the Confidence and Balance Scale, Fugl-Meyer Assessment of Physical Performance (FMA), Modified Ashworth Scale (MAS), Postural Stroke Scale for post-stroke patients (PSS), Time up and go test (TUG), 10-Meter gait test, Stroke Scale Barthel and weight transfer in the affected lower limb. Participants were treated in 12 walking training sessions on the treadmill with 1 kg added to the ankle of the lower limb. Results: There were variations between the 3 times for gait time (p= 0.005), FMA (p= 0.002), Activities-specific Balance Confidence Scale (ABC scale) (p= 0.007) and EAPA (p= 0.042). Conclusion: Treadmill therapy and weight addition in the healthy limb revealed improvement in motor function, balance in orthostatism and walking speed.